MENINGKATKAN PELAYANAN MASYARAKAT MELALUI PENINGKATAN KINERJA ANGGOTA PADA ORGANISASI NIRLABA - Setyawan, Iwan; Fatoni, Aris (2020)
The purpose of this study was to determine the contribution of organizational commitment, job involvement and training in improving the performance of members of non-profit organizations and their impact on improving the quality of service to the community. The survey method was used to obtain primary data through distributing questionnaires, with a sample covering members of the organization and congregation who were selected by simple random sampling. Data analysis used structural equation modeling (SEM) Partial Least Squares Second Order Confirmatory with the help of SmartPLS 3.2 software. The results of the study found that organizational commitment and training had a positive and significant effect on member performance and had a positive impact on service quality. Meanwhile, job involvement does not have a direct effect on members 'performance, but indirectly has a significant effect on members' performance through organizational commitment.